Respuesta :

What you would do is plug in -3 where x is.
h(x)=6(-3)*2-2(-3)+12
You then would solve the equation.
*Remember P.E.M.D.A.S.*
6(-3)*2-2(-3)+12  - Multiply 6(-3) & 2(-3) together.
-18*2-6+12 - Multiply -18*2 together.
-36-6+12 -Add 12 to -36
-24-6 -Subtract
-30

Hope This helps! :)

Answer:

72

Step-by-step explanation:

Parentheses Exponents Multiplication Division Addition Subtraction

h(-3) = 6(-3)^2 - 2(-3) + 12

E h(-3) = 6(9) - 2(-3) + 12

M h(-3) = 54 - (-6) +12

A h(-3) = 66 - (-6)

S h(-3) = 72